Economic and legal bases of administration of the customs-tariff mechanism - Федотов, Олексій Павлович; Федотов, О. П.; Федотов, Алексей Павлович; Fedotov, Oleksii P.; Ненько, Сергій Сергійович; Ненько, С. С.; Ненько, Сергей Сергеевич; Nenko, Serhii S.; Щедрова, Галина Петрівна; Щедрова, Г. П.; Щедрова, Галина Петровна; Shchedrova, Halyna P. (Baltija Publishing, 2022)
The subject of the study is public relations in the field of administrative and legal regulation of the customs and tariff mechanism of foreign economic activity. Methodology. The instrumental and methodological apparatus of the research is formed by the applied methods of economic analysis of the activities of organizations, statistical methods, selective observation, the method of economic modelling, grouping, generalization, expert assessments, methods of economic theory, marketing, etc. The aim of the article is to analyse the administrative and legal aspects of the mechanism of customs and tariff regulation in modern conditions in Ukraine and the world. The research results in a comprehensive consideration of the system of administrative and legal regulation of the customs tariff mechanism in Ukraine and the world, within which: the impact of the customs tariff mechanism on foreign economic activity is assessed; the modern foundations and principles of tariff benefits and protectionism policy are highlighted; the analysis of the administrative legislation of the studied area is carried out; weaknesses and problems of administrative and legal support of the customs tariff mechanism are identified, and ways of their solution are proposed. Conclusion. Customs and tariff regulation acts, on the one hand, as an effective regulator that promotes greater openness of the market, on the other - as the most common foreign trade instrument of protectionism. Therefore, improving the problems of customs and tariff regulation in modern conditions is simply necessary to overcome the crisis phenomena in the domestic economy and ensure the economic security of the state. After all, it requires the determination of the maximum level of tariff rates of import duties, which, under the normal functioning of the economy, will not increase and may be reduced in the future. Such plans may shock many sectors of the domestic economy. These primarily include agriculture, the food industry, the pharmaceutical industry, and the leather and shoe industry. Customs and tariff regulation is designed to promote the goals and objectives of foreign economic activity, as well as ensuring the security of the country and protecting national interests. The methods of customs and tariff regulation are more consistent with the nature of market relations and therefore play a major role in regulating foreign economic activity. In modern conditions, customs and tariff regulation can and should become an effective tool for mitigating and gradually overcoming crisis phenomena in the economy.

Предмет дослідження – суспільні відносини у сфері адміністративно-правового регулювання митно-тарифного механізму зовнішньоекономічної діяльності. Методологія. Інструментально-методичний апарат дослідження формують прикладні методи економічного аналізу діяльності організацій, статистичні методи, вибіркове спостереження, метод економічного моделювання, групування, узагальнення, експертні оцінки, методи економічної теорії, маркетингу тощо. Метою статті є аналіз адміністративно-правових аспектів механізму митно-тарифного регулювання в сучасних умовах в Україні та світі. Результатом дослідження є комплексний розгляд системи адміністративно-правового регулювання митно-тарифного механізму в Україні та світі, в рамках якого: оцінено вплив митно-тарифного механізму на зовнішньоекономічну діяльність; висвітлено сучасні основи та принципи тарифних пільг та політики протекціонізму; проведено аналіз адміністративного законодавства досліджуваної області; виявлено слабкі місця та проблеми адміністративно-правового забезпечення митно-тарифного механізму та запропоновано шляхи їх вирішення. Висновок. Митно-тарифне регулювання виступає, з одного боку, як ефективний регулятор, що сприяє більшій відкритості ринку, з іншого – як найпоширеніший зовнішньоторговельний інструмент протекціонізму. Тому вдосконалення проблем митно-тарифного регулювання в сучасних умовах просто необхідно для подолання кризових явищ у вітчизняній економіці та забезпечення економічної безпеки держави. Адже це вимагає визначення максимального рівня тарифних ставок імпортних мит, які за нормального функціонування економіки не підвищаться і можуть бути знижені в майбутньому. Такі плани можуть шокувати багато секторів вітчизняної економіки. У першу чергу це сільське господарство, харчова промисловість, фармацевтична промисловість, шкіряно-взуттєва промисловість. Митно-тарифне регулювання покликане сприяти досягненню цілей і завдань зовнішньоекономічної діяльності, а також забезпеченню безпеки країни та захисту національних інтересів. Методи митно-тарифного регулювання більшою мірою відповідають природі ринкових відносин і тому відіграють велику роль у регулюванні зовнішньоекономічної діяльності. У сучасних умовах митно-тарифне регулювання може і повинно стати ефективним інструментом пом’якшення та поступового подолання кризових явищ в економіці.
Nenko S. Economic and legal bases of administration of the customs-tariff mechanism / S. Nenko, O. Fedotov, H. Shchedrova // Baltic journal of economic studies. - Vol. 8. - Iss. 1. - Baltija Publishing, 2022. - P. 103-110.
Keywords: customs regulation; tariff regulation; administrative and legal regulation; customs tariff; customs post; foreign economic activity; national economy; international economy; international law; administrative law; митне регулювання; тарифне регулювання; адміністративно-правове регулювання; митний тариф; митний пост; зовнішньоекономічна діяльність; національне господарство; міжнародна економіка; міжнародне право; адміністративне право; Research Subject Categories::LAW/JURISPRUDENCE